2017
DOI: 10.1007/s10549-017-4126-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of volumetric breast density in Chilean premenopausal women

Abstract: DXA is an alternative method to measure volumetric BD; thus, it could be used to continuously monitor BD in adult women in follow-up studies or to assess BD in young women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…The between women associations of attained premenopausal BMI and breast density observed in this study were consistent with previous studies. High BMI is associated with high dense volume [33][34][35], but the correlation between BMI and dense area is less strong, and often close to zero [36][37][38][39]. These differences are likely to be a result of volumetric measures representing breast tissue more accurately than area-based methods by accounting for breast thickness and overlapping tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The between women associations of attained premenopausal BMI and breast density observed in this study were consistent with previous studies. High BMI is associated with high dense volume [33][34][35], but the correlation between BMI and dense area is less strong, and often close to zero [36][37][38][39]. These differences are likely to be a result of volumetric measures representing breast tissue more accurately than area-based methods by accounting for breast thickness and overlapping tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These differences are likely to be a result of volumetric measures representing breast tissue more accurately than area-based methods by accounting for breast thickness and overlapping tissue. Additionally, since the breast is a deposit for adipose tissue, high attained BMI is strongly associated with high levels of breast fat area [36][37][38][39] and breast fat volume [33,34], which in turn leads to an inverse association between BMI and both percent dense area [36][37][38][39][40][41] and percent dense volume [33][34][35]42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Raw images were saved in low and high energy, and AFGV and %FGV were calculated using software from one of the investigators (Shepherd) with intra-and interrater readings all had ICC values greater than 0.9. Recently, Pereira et al found that in 200 GOCs mothers, the precision of the DXA data after the repositioning of the left breast was 2.8%, and the ICCs for %FGV and AFGV were > 0.9 19 .…”
Section: Methodsmentioning
confidence: 99%
“…One of the major difficulties is the challenge of measuring BD in young women. Recently, dual energy X-ray absorptiometry (DXA) technology has been developed for this purpose and has been shown to be valid, reproducible and accurate (precision of 2.8%) 19 with a minimal dose of radiation; therefore, DXA can be used in young women 20 . Thus, by investigating a Chilean cohort of mothers and daughters, our study aimed to assess the relation between EGWG according to the 2009 IOM guidelines 6 and BD estimated by DXA in the offspring at the end of puberty (B4).…”
mentioning
confidence: 99%
“…The epidemiological evidence on the association between the smoking status and breast density has been limited and inconsistent so far. Of the 15 epidemiological studies, most have evaluated the relationship with the current smoking status and found a lower mammographic density among current smokers when compared to former smokers or non-smokers [12][13][14][15][16][17][18][19][20][21][22]. The association between the lifelong smoking duration or intensity and breast density has been rarely addressed [4,[12][13][14][15].…”
Section: Questionnaire and Anthropometric Measurementsmentioning
confidence: 99%